Larvicidal activity of acacia nilotica extracts and isolation of D-pinitol - a bioactive carbohydrate - Chaubal, Rohini; Pawar, P. V.; Hebbalkar, G. D.; Tungikar, V. B.; Puranik, Vedavati G.; Deshpande, V. H.; Deshpande, N. R. (Chemistry & Biodiversity, 2005)
A low-molecular-weight, sugar-like compound other than glucose, fructose, sucrose, or myo-inositol showing lipophilic nature was isolated from the EtOH extract of Acacia nilotica. The structure of the compound was determined by spectral methods. This alicyclic polyalcohol was found to be D-pinitol (- 3-O-methyl-D-chiro-inositol; 1). The configuration of the compound was confirmed by single-crystal X-ray analysis. The compound I is known from Soybean, Australian mangroves, Fagonia indica, A rachis hypogaea, etc., but we have isolated this compound for the first time from the aerial parts of A. nilotica. Very few references have been cited for compound I for its entomological activity, and there are no reports on mosquitoes. Therefore, the crude extracts of A. nilotica were tested for its biological activity against mosquito larvae. Acetone extract at 500-ppm concentration showed chronic toxicity against Aedes aegypti and Culex quinquefasciatus IVth instar mosquito larvae. Such a biological activity has been observed for the first time for this plant. This study could be a stepping stone to a solution for destroying larval species as well as consumption of such a widely grown, problem weed, A. nilotica. This larvicidal agent, since it is derived from plant, is eco-friendly, cost effective, non-hazardous to nontarget organisms and would be safe unlike commercially available insecticides.

Insect-repellent and mosquitocidal effects of noreremophilane- and nardoaristolone-based compounds - Handore, K. L.; Kalmode, H. P.; Sayyad, S.; Seetharamsingh, B.; Gathalkar, G.; Padole, S.; Pawar, P. V.; Joseph, M.; Sen, A.; Reddy, D. S. (ACS Omega, 2019)
Here, we disclose novel mosquito-repellent synthetic hydrindanes based on noreremophilanes and nardoaristolone B which show increased activity against adult females of Aedes aegypti. The noreremophilanes and nardoaristolone B with hydrindane skeleton are structurally related to nootkatone with decalin skeleton, a well-studied natural product extracted from a grape fruit. Out of our library of compounds synthesized based on the noreremophilanes and nardoaristolone B scaffolds, NDS-100598 (compound 20) exhibits higher repellent and knock-down effects at a very low concentration (0.25 mg/cm2), while a few analogues showed considerably enhanced activity compared to racemic nootkatone. This is the first report documenting insect-repellent and knock-down activity of the noreremophilanes class of compounds.